Cone Beam Computed Tomography Analysis of Incidental Maxillary Sinus Pathologies in North Indian Population - Sangeeta S Malik; Aarfa Nasim; Ravi Prakash S Mohan; Nagaraju Kamarthi; Sumit Goel; Swati Gupta (Wolters Kluwer Medknow Publications, 2017)
Introduction: Maxillary sinus can be visualized in both two-dimensional and three-dimensional images. Computed tomography (CT) is considered the gold standard method for the examination of maxillary sinus. Cone beam computed tomography (CBCT) addresses the limitation of CT and provides many dental advantages. It can provide valuable knowledge about the pathology with limited exposure and low cost compared with other imaging used for diagnostic purposes. Aims and Objectives: The aim of the study is to analyze the prevalence of pathological changes in maxillary sinus of asymptomatic cases using CBCT for diagnostic purposes. Materials and Methods: This retrospective study evaluated 231 patients for incidental maxillary sinus pathologies. Pathological findings were categorized as mucosal thickening, polypoid mucosal thickening, radiopacification, and no pathological findings. Evaluation of pathological findings was done using factors of age and gender. Results: The present study showed 86 cases with maxillary sinus pathology and 145 cases with no pathological findings. Patients with maxillary sinus pathology were mostly diagnosed with mucosal thickening on both sides. In right maxillary sinus, 45 cases (52.3%) showed mucosal thickening, and on the left side 36 cases (41.9%) were diagnosed with mucosal thickening. Among 86 cases reported, 20 right maxillary sinus (23.3%) and 25 left maxillary sinus (29.1%) showed no signs of pathology. Conclusion: The incidental maxillary sinus pathologies are highly prevalent in asymptomatic patients. Therefore, oral radiologists should be aware of these incidental findings which will help in early diagnosis and treatment of disease.